PIDOTIMOD IN TREATMENT OF ACUTE RESPIRATORY INFECTION IN FREQUENTLY AILING CHILDREN - F.S. Kharlamova; V.F. Uchaikin; O.V. Kladova; S.L. Bevza (Вопросы современной педиатрии, 2009)
This trial studied effectiveness and safety of pidotimoid (Imunorix) in complex treatment of children with acute respiratory infection (ARI). Treatment with pidotimoid during 2 weeks (n = 30) resulted in lesser duration of fever and intoxication symptoms, and symptoms of laryngo-tracheitis, compared to control group (n = 30). Besides, children from pidotimoid group showed more rapid transformation of dry cough to hydrated cough, and decrease of its intensity. This beneficial change was accompanied by improvement of microbiocenosis. Effectiveness of pidotimoid was estimated by 73% of doctors as «good» (67% in control group). There was no any complication, related to treatment with this medication. The rate of repeated cases of ARI was three times lower then in control group in 6 months. All patients with ARI had no recurrent laryngeal stenosis.Key words: frequently ailing children, acute respiratory infection, treatment, prophylaxis, pidotimoid.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2009;8(2):27-33)